HUBUNGAN PEMBERIAN SUPLEMEN ZAT BESI (FE) PADA IBU HAMIL DENGAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSUD ABDUL WAHAB SJAHRANIE SAMARINDA - Iriyani K (Jurnal Ilmiah Manuntung, 2016)
Babies of low birth weight is a baby who weighed less than 2500 grams. Low birth weight is caused by several factors i.e. a premature birth, small size baby, and IUGR (intra-uterine growth retardation). The purpose of this study was to determine the correlation between supplemental iron (Fe) in pregnant women and low birth weight. The design research is quantitative method with Case Control approach using 116 samples from 58 cases and 58 control groups with a ratio of 1:1 for both sexes. The sampling method is purposive Sampling. Dana analyzed using Chi Square correlation test with CI 95% at value of α of 5%. The results showed that there was a correlations between supplemental Fe in pregnant women (ρ value = 0,001 with OR = 8.25) with low birth weight.  To reduce the high incidence of low birth weight, pregnant women are suggested to take Fe supplements or taking high content Fe meal everyday.